2022
DOI: 10.1111/jvp.13089
|View full text |Cite
|
Sign up to set email alerts
|

Robenacoxib pharmacokinetics in sheep following oral, subcutaneous, and intravenous administration

Abstract: Changing moral and ethical considerations have led to societal demands for better agricultural practices and enhanced wellbeing for food producing animals all around the world. In this perspective, proper pain management is a critical component of promoting farm animal welfare. Pain alters behavior, autonomic, and neuroendocrine function. It causes a depressed mood and is a common cause of animal welfare violations (Steagall et al., 2021). In farm animals, chronic pain, for example, was shown to reduce food co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…These findings suggest that the subcutaneous robenacoxib is absorbed to a higher extent than the oral administration. A recent study in sheep demonstrated that true mean oral bioavailability of robenacoxib was low at only 16.58% (Fadel et al, 2022), which suggests that the relative bioavailability calculated in this study may be comparable to true bioavailability of robenacoxib in rabbits. In dogs, absolute bioavailabilities have been determined and demonstrated that after oral administration when fasted, there was a high bioavailability (84%) but a markedly reduced bioavailability when fed (62%) (Jung et al, 2009).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These findings suggest that the subcutaneous robenacoxib is absorbed to a higher extent than the oral administration. A recent study in sheep demonstrated that true mean oral bioavailability of robenacoxib was low at only 16.58% (Fadel et al, 2022), which suggests that the relative bioavailability calculated in this study may be comparable to true bioavailability of robenacoxib in rabbits. In dogs, absolute bioavailabilities have been determined and demonstrated that after oral administration when fasted, there was a high bioavailability (84%) but a markedly reduced bioavailability when fed (62%) (Jung et al, 2009).…”
Section: Discussionsupporting
confidence: 54%
“…Despite the short elimination half-life in dogs and cats, dosing frequency is once daily due to the prolonged duration of action in patients with peripheral inflammation because of the selectivity of robenacoxib for inflammatory sites (Fadel et al, 2022). Since rabbits have a longer elimination half-life, it may be considered that dosing frequency may be even further extended, though further study would be needed to investigate this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No systemic or local adverse effects were observed following the various routes of administration of RX at a dose of 2–4 mg/kg in goats. It was the case as well in sheep (Fadel et al, 2022), dogs (Jung et al, 2009), cats (King et al, 2013), rabbits (Jeffrey et al, 2023), rats (King et al, 2009) and rainbow trout (Raulic et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Even though the IV route for RX is not recommended, it was critical to evaluate this route in order to determine true clearance, volume of distribution and absolute bioavailability for the EV administrations. As in Fadel et al (2022), the IV dose was purposefully chosen lower than for the other routes of administration to reduce potential systemic toxicity and collateral effects. Although dose‐independent pharmacokinetics cannot be completely ruled out in goats, RX PK was found to be dose‐dependent with linear plasma drug concentrations in dogs (Borer et al, 2017; King et al, 2011; Schmid et al, 2010).…”
Section: Discussionmentioning
confidence: 99%